Lippia sidoides Cham. Compounds Induce Biochemical Defense Mechanisms Against Curvularia lunata sp. in Maize Plants - Bruna Leticia Dias; Talita Pereira de Souza Ferreira; Mateus Sunti Dalcin; Dalmarcia de Souza Carlos Mourão; Paulo Ricardo de Sena Fernandes; Taila Renata Neitzke; João Victor de Almeida Oliveira; Tiago Dias; Luis Oswaldo Viteri Jumbo; Eugênio Eduardo de Oliveira; Gil Rodrigues dos Santos (J)
Corn (Zea mays L.) productivity is often compromised by phytosanitary challenges, with fungal disease like Curvularia leaf spot being particularly significant. While synthetic fungicides are commonly used, there is growing interest in exploring alternative compounds that are effective against pathogens, ensure food safety, and have low toxicity to non-target organisms. In this study, we examined the biochemical changes in corn plants treated with Lippia sidoides essential oil and its major compound, thymol. Both treatments serve as preventive measures for inoculated plants and induced resistance. We tested five concentrations of each product in in vivo experiments. After evaluating the area under the disease progress curve, we analyzed leaf samples for enzymatic activities, including superoxide dismutase, catalase, ascorbate peroxidase, and chitinase. Phytoalexin induction was assessed using soybean cotyledons and sorghum mesocotyls. Cytotoxicity tests revealed lower toxicity at concentrations below 50 µL/mL. Both essential oil and thymol stimulated the production of reactive oxygen species, with thymol primarily activating catalase and L. sidoides oil increasing ascorbate peroxidase levels. Both thymol and L. sidoides were also key activators of chitinase. These findings suggest that L. sidoides essential oil and thymol are promising candidates for developing biological control products to enhance plant defense against pathogens.